Efficacy and safety of trifluridine/tipiracil plus bevacizumab and trifluridine/tipiracil or regorafenib monotherapy for chemorefractory metastatic colorectal cancer: a retrospective study. (April 2021) - Chida, Keigo; Kotani, Daisuke; Nakamura, Yoshiaki; Kawazoe, Akihito; Kuboki, Yasutoshi; Shitara, Kohei; Kojima, Takashi; Taniguchi, Hiroya; Watanabe, Jun; Endo, Itaru; Yoshino, Takayuki
Background: The C-TASK-FORCE phase I/II and Danish randomized phase II trials reported the promising efficacy of trifluridine/tipiracil (TAS102) plus bevacizumab (BEV) in patients with chemorefractory metastatic colorectal cancer (mCRC). However, there had been no direct comparative phase III trial to compare the efficacy between TAS102 plus BEV and standard therapy with either TAS102 or regorafenib monotherapy. Methods: We retrospectively reviewed the medical records of patients with mCRC who received TAS102 plus BEV, TAS102 monotherapy, or regorafenib monotherapy after standard chemotherapies during 2013–2019. Results: Patients received TAS102 plus BEV ( n = 139), TAS102 monotherapy ( n = 153), or regorafenib monotherapy ( n = 133). With a median follow-up of 25.3 months, median overall survival (OS) was 11.5 months [95% confidence interval (CI), 9.9–13.9] for TAS102 plus BEV, 8.1 months (95% CI, 6.8–9.2) for TAS102 monotherapy, and 6.8 months (95% CI, 5.7–8.5) for regorafenib monotherapy. The hazard ratios were 0.67 (95% CI, 0.51–0.88) for TAS102 plus BEV versus TAS102 monotherapy and 0.71 (95% CI, 0.54–0.94) for TAS102 plus BEV versus regorafenib monotherapy. Median progression-free survival (PFS) was 4.4 months (95% CI, 3.7–5.4) for TAS102 plus BEV, 2.5 months (95% CI, 1.6–2.3) for TAS102 monotherapy, and 2.1 months (95% CI, 1.6–2.3) for regorafenib monotherapy. The hazard ratios were 0.57 (95% CI, 0.45–0.73) for TAS102 plus BEV versus TAS102 monotherapy and 0.44 (95% CI, 0.34–0.58) for TAS102 plus BEV versus regorafenib monotherapy. On multivariate analysis, TAS102 plus BEV was independently correlated with better OS and PFS. No unexpected adverse events were observed in any group. Conclusion: Our study shows that OS and PFS are longer in patients treated with TAS102 plus BEV than in those treated with TAS102 or regorafenib monotherapy.